Pengaruh Kemudahan Penggunaan dan Gaya Hidup Terhadap Perilaku Konsumtif Pengguna Shopee Paylater di Kalangan Gen Z di Kota Tanjungpinang - Ariyanto, Reza; Jintar, Catri; Novia, Siti Arita (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of Ease of Use and Lifestyle on the consumption behaviour of Shopee PayLater users among Gen Z in Tanjungpinang City. The research design is explanatory quantitative, with sampling conducted using purposive sampling (96 respondents). Primary data were collected through a Likert-scale questionnaire, supplemented by secondary data from the literature; all data were analysed using SPSS version 27. The data analysis stages included instrument validity testing, testing of classical assumptions, multiple linear regression analysis, t-tests, F-tests, and the Coefficient of Determination (R²). The results of the study indicate that the variables Ease of Use (X1) and Lifestyle (X2) jointly have a positive and significant effect on Consumption Behaviour (Y). This is evidenced by a calculated F-value of 22.185, which is greater than the critical F-value (3.09), as well as a p-value of